Cryptic DNA-binding domain in the C terminus of RNA polymerase II general transcription factor RAP30. - Tan, S (1994)
The C terminus of mammalian transcription factor RAP30 has been found to be a cryptic DNA-binding domain strikingly similar to the C-terminal DNA-binding domain present in conserved region 4 of members of the sigma 70 family of bacterial sigma factors. This RAP30 domain shares strongest sequence similarity with the DNA-binding domain present in region 4 of Bacillus subtilis sporulation-specific sigma K. Like the region 4 DNA-binding activity of Escherichia coli sigma 70, the RAP30 C-terminal DNA binding activity is masked in intact RAP30 but is readily detectable when the RAP30 C terminus is expressed as a fusion protein. Consistent with a role for RAP30 DNA-binding activity in transcription, mutations that abolish DNA binding also abolish transcription. Therefore, RAP30 may function at least in part through the action of an evolutionarily ancient DNA-binding domain that first appeared prior to the divergence of bacteria and eukaryotes.